The Biology of Mesopelagic Fishes and Their Catches (1950–2018) by Commercial and Experimental Fisheries - Daniel Pauly; Chiara Piroddi; Lincoln Hood; Nicolas Bailly; Elaine Chu; Vicky Lam; Evgeny A. Pakhomov; Leonid K. Pshenichnov; Vladimir I. Radchenko; Maria Lourdes D. Palomares (Journal of Marine Science and Engineering, 2021)
Following a brief review of their biology, this contribution is an attempt to provide a global overview of the catches of mesopelagic fishes (of which 2.68 million tonnes were officially reported to the FAO) throughout the world ocean from 1950 to 2018, to serve as a baseline to a future development of these fisheries. The overview is based on a thorough scanning of the literature dealing with commercial or experimental fisheries for mesopelagics and their catches, and/or the mesopelagic bycatch of other fisheries. All commercial (industrial and artisanal) fisheries for mesopelagic fishes were included, as well as experimental fisheries of which we were aware, while catches performed only to obtain scientific samples were omitted. The processes of generating bycatch and causing discards are discussed, with emphasis on Russian fisheries. From peer-reviewed and gray literature, we lifted information on mesopelagic fisheries and assembled it into one document, which we then summarized into two text tables with catch data, one by country/region, the other by species or species groups.